Applications of sports data to study decision making - Balafoutas, Loukas; Chowdhury, Subhasish M.; Plessner, Henning (Journal of economic psychology, 2019)
The features and determinants of human decision making, especially under competitive environments, have been a central theme of research in economics and psychology alike. This special issue centers on applying sports data to understand behavior and decision making in competitive environments. In particular, we assemble original research with sports data that provides us with insights into hitherto unanswered questions relating to various strategic and psychological aspects of decision making.